Two-dimensional binary colloidal crystals formed by particles with two different sizes - Masahide Sato (Scientific Reports, 2022)
Abstract The formation of $$AB_2$$ AB 2 type two-dimensional binary colloidal crystals was studied by performing Monte Carlo simulations with two different size particles. The effect of interactions between particles and between particles and a wall, and the particles size ratios on the formation of $$AB_2$$ AB 2 structure were examined. $$AB_2$$ AB 2 structures formed efficiently when the interaction between equivalently sized particles was smaller than that between differently sized particles. To create $$AB_2$$ AB 2 on a wall, it was necessary to choose a suitable particles size ratios, and the attraction between the particles and the wall was greater than that between particles.